2010
DOI: 10.1590/s0104-42302010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and metabolic syndrome in a population of young students from the National University of Colombia

Abstract: SummaryObjective. To estimate prevalence and distribution of cardiovascular risk factors and Metabolic Syndrome (MS) in young individuals admitted to the National University of Colombia in Bogotá.MethOds. An analytic cross-sectional study was conducted in a sample of 249 individuals of both genders aged 15 to 20 years. A questionnaire was personally administered to collect demographic, socioeconomic, smoking, perinatal, and women's health data. Anthropometric measurements, blood pressure, and a fasting blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
8
26
0
5
Order By: Relevance
“…Significant differences between genders were not observed, but it was associated with age, indicating that the higher the age, the higher the rates of excessive weight, which may predispose one to adult obesity. (16)(17)(18) The prevalence of a sedentary lifestyle, compared to that recommended by the international literature, was higher, which differs from a national study that showed more than 60% of sedentary. Thus, it is understood that the practice of physical activity is still not experienced by students, especially girls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Significant differences between genders were not observed, but it was associated with age, indicating that the higher the age, the higher the rates of excessive weight, which may predispose one to adult obesity. (16)(17)(18) The prevalence of a sedentary lifestyle, compared to that recommended by the international literature, was higher, which differs from a national study that showed more than 60% of sedentary. Thus, it is understood that the practice of physical activity is still not experienced by students, especially girls.…”
Section: Discussionmentioning
confidence: 90%
“…(24) In a national study, the value is lower than what has been described (13.3%), and remains higher in males. (16) The prevalence of low HDL-c, even small, should be reversed by actions that stimulate its increase among students, as increased levels of HDL-c decrease the relative risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…En Colombia, la prevalencia de Diabetes Mellitus tipo 2 (DM2) varía entre 4% y 8%, siendo menor en las zonas rurales (2%), de lo cual se desprende la importancia de factores ligados a los procesos sociales y económicos de urbanización, como dieta rica en calorías y disminución de la actividad físi-ca que pueden generar obesidad, la cual ocurre en más del 30% de los habitantes urbanos y Síndrome Metabólico presente en el 20-35% de la población (1). La intolerancia a la Glucosa es casi tan frecuente como la DM2.…”
Section: Introductionunclassified
“…La intolerancia a la Glucosa es casi tan frecuente como la DM2. En 2005-2006, se adelantó una investigación en universitarios que registró prevalencia de glicemia en ayunas ≥ 100 mg/dl, en 8.4%, además de intolerancia a la Glucosa de 0.8% (1). Según el análisis de situación de salud para Colombia 2014 las enfermedades hipertensivas fueron responsables del 9,35% (22.476) de los decesos por enfermedades del sistema circulatorio en hombres, equivaliendo al 4,82% del total de muertes en el grupo de causas.…”
Section: Introductionunclassified
“…En los andes peruanos, especialmente en zonas urbanas, los individuos en diversos escenarios (hogar, escuelas, centros de formación y laborales) están expuestas a la occidentalización de la dieta, formas de vida sedentarias, y otros cambios culturales (5) . En este contexto, y frente a la limitada evidencia (8,9,10) sobre la magnitud, perfil fenotípico y características asociadas al SM; el presente estudio busca contribuir con la detección temprana y posible prevención del SM mediante la caracterización fenotípica en adolescentes y adultos jóvenes residentes de zonas alto andinas.…”
Section: Introductionunclassified